Concordance of chest x-ray with chest CT by body mass index - Heston, Thomas F.; Jiang, John Y. (PeerJ, 2023)
Introduction Patients with suspected thoracic pathology frequently get imaging with conventional radiography or chest x-rays (CXR) and computed tomography (CT). CXR include one or two planar views, compared to the three-dimensional images generated by chest CT. CXR imaging has the advantage of lower costs and lower radiation exposure at the expense of lower diagnostic accuracy, especially in patients with large body habitus. Objectives To determine whether CXR imaging could achieve acceptable diagnostic accuracy in patients with a low body mass index (BMI). Methods This retrospective study evaluated 50 patients with age of 63 ± 12 years old, 92% male, BMI 31.7 ± 7.9, presenting with acute, nontraumatic cardiopulmonary complaints who underwent CXR followed by CT within 1 day. Diagnostic accuracy was determined by comparing scan interpretation with the final clinical diagnosis of the referring clinician. Results CT results were significantly correlated with CXR results (r = 0.284, p = 0.046). Correcting for BMI did not improve this correlation (r = 0.285, p = 0.047). Correcting for BMI and age also did not improve the correlation (r = 0.283, p = 0.052), nor did correcting for BMI, age, and sex (r = 0.270, p = 0.067). Correcting for height alone slightly improved the correlation (r = 0.290, p = 0.043), as did correcting for weight alone (r = 0.288, p = 0.045). CT accuracy was 92% (SE = 0.039) vs. 60% for CXR (SE = 0.070, p < 0.01). Conclusion Accounting for patient body habitus as determined by either BMI, height, or weight did not improve the correlation between CXR accuracy and chest CT accuracy. CXR is significantly less accurate than CT even in patients with a low BMI.
Keywords: Diagnostic imaging; Chest x-ray; Computed tomography; Body mass index